Analysis Of Moral Values In Lencana Alia™ Children Story By Esti Asmala - M Ridwan; Mulasih Mulasih (Universitas PGRI Yogyakarta, 2022)
This research aimed to analyze the exemplary values in 'Lencana Alia' story book by Esti Asmala. This research was carried out with a qualitative method. The result revealed that Asmala combined symbolic modeling technique and positive reinforcement to give an understanding of exemplary values that children can practice. The symbolic modeling technique included the character activities that showed some moral values such as independence, cleanliness, responsibility, commitment, social care, and honesty. Then, an example of positive reinforcement was given to encourage children in the form of a badge based on the character they successfully played. Besides, children were also taught to recognize critical situations to see a situation that is more appropriate or favorable to their ego.